Impact of graphite admixture on electrical properties of alkali-activated slag mortars - Kusák, Ivo; Luňák, Miroslav; Rovnaník, Pavel (EDP Sciences, 2017)
One of the objectives of the applied research's striving consists in providing the users with new slag-mortar-based materials. Basic research, in its turn, aims at examining the newly created materials from the viewpoint of all possible testing methods. Slag mortar specimens were subjected to electrical analysis carried out by means of an ZNC vector analyser and an SPEAG-made DAK-12 coaxial probe within the frequency range from 100 MHz to 3GHz and, furthermore, a dedicated automatically measuring device within the frequency range from 40 Hz to 1 MHz. The frequency spectra of interest were measured on various copolymer specimens differing from each other by the content of the carbon powder. Higher graphite powder content increases the electrical conductivity of cement/slag-based building materials, which thus become easier to measure by means of electromagnetic measuring methods. Carbon admixture may also improve the material's antistatic properties.

One of the objectives of the applied research's striving consists in providing the users with new slag-mortar-based materials. Basic research, in its turn, aims at examining the newly created materials from the viewpoint of all possible testing methods. Slag mortar specimens were subjected to electrical analysis carried out by means of an ZNC vector analyser and an SPEAG-made DAK-12 coaxial probe within the frequency range from 100 MHz to 3GHz and, furthermore, a dedicated automatically measuring device within the frequency range from 40 Hz to 1 MHz. The frequency spectra of interest were measured on various copolymer specimens differing from each other by the content of the carbon powder. Higher graphite powder content increases the electrical conductivity of cement/slag-based building materials, which thus become easier to measure by means of electromagnetic measuring methods. Carbon admixture may also improve the material's antistatic properties.
Impact of graphite admixture on electrical properties of alkali-activated slag mortars
Keywords: Electrical measurements; geopolymer structure; dielectric losses; permittivity; conductivity; graphite; Electrical measurements; geopolymer structure; dielectric losses; permittivity; conductivity; graphite